Characterization and biological screening of the culturable endophytic actinomycetes from Garcinia cowa Roxb. - Tilarux, P.; Suwanposri, A.; Anartngam, P.; Supong, K. (International Journal of Agricultural Technology, 2025)
Actinomycetes associated with plants are relatively interactive sources of potential natural products. Two culturable endophytic actinomycetes strains, GcL-T1-1 and GcLT2-2, were isolated from a leaf of cowa (Garcinia cowa Roxb.). Determination of morphological and physiological properties, strains GcL-T1-1 and GcLT2-2, formed filament cells and presented spores on the mycelia which were classified to actinomycete group. In addition, strain GcL-T1-1 belonged to Streptomyces based on morphological and chemotaxonomic characteristics, which contained LL- diaminopimelic acid in peptidoglycan of cell wall. The molecular identification using similarity value of 16S rRNA gene, a non-streptomycete GcL-T2-2 was classified within the family Micromonosporaceae, genus Micromonospora that presented the highest similarity with M. schwarzwaldensis HKI0641T (99.93%), follow with M. haikouensis 232617T (99.23%), M. humi DSM 45647T (99.16%), M. maritima D10-9-5T (99.16%), M. sediminicola DSM 45794T (99.16%), M. oryzae CP2R9-1T (99.16%) and M. mangrove 2803GPT1-18T (99.16%). In addition, neighbour-joining phylogeny confirmed that strain GcL-T2-2 formed a phyletic line within Micromonospora. Biological screening for antimicrobial and cytotoxic activities, ethyl acetate crude extract of Micromonospora sp. GcL-T2-2 exhibited activity against Bacillus cereus and NCI-H187 tumor cells at MIC of 50 µg/mL and IC50 of 48.12 µg/mL, respectively. The Garcinia cowa associated Streptomyces strain GcLT1-1 exhibited cytotoxic activity with NCI-H187 tumor cells at the IC50 value of 43.20 µg/mL. However, antagonistic activity against Alternaria brassicicola and Colletotrichum acutatum was an inactive result that displayed MIC value of more than 50 µg/mL.